PENGARUH LABA DAN KOMPONEN ARUS KAS TERHADAP RETURN SAHAM (Studi Empiris Pada Perusahaan terdaftar di BEI Periode Tahun 2007–2009) - Nur, Aini (Jurnal Ilmiah Telaah Manajemen, 2009)
This study aims to provide empirical evidence of the influence of the information published financial statements, the accounting profit, cash flow components comprising cash flows from operating activities, cashflows from investing activities and cash flows from financing akrivitas on stock returns manufktur companies listed in Indonesia Stock Exchange (IDX). During the observation period of 2006 - 2009 This study used a sample of 99 listed companies amounted selected using purposive sampling method. The data in this study is a secondary data obtained from the Indonesian Capital Market Directory and IDX Corner at the Faculty of Economics, University of Diponegoro in Semarang. The statistical methods used to analyze the data using multiple regression analysis. Variable used is earnings accounting proxy retun on assets (ROA), a component of cash flows from the activities of the Operating Cash Flow, Cash Flow from Investing activities, cash flow from financing activities as an independent variable, while the Stock Return as the dependent variable. Of testing the hypothesis, this study produced findings that variable accounting profit / ROA has a significant positive effect on stock returns, the variable Cash Flows from Operating Akrivitas not have asignificant influence on stock returns, while Cash Flows from Investing Activities and Cash Flow from Financing activities influence significant positive stock returns.Keywords: Accounting Information, Accounting Earnings - ROA, Cash Flow Components and Stock Return.